Thermodynamic aspects of polymer–surfactant interactions: Gemini (16-5-16)-PVP-water system - Naved Azum; Abdullah M. Asiri; Malik Abdul Rub; Abdulrahman O. Al-Youbi; Anish Khan (Arabian Journal of Chemistry, 2016)
The interaction between polyvinylpyrrolidone (PVP) and gemini surfactant (16-5-16) in aqueous solution has been analyzed using conductometry. From conductivity data the critical aggregation concentration (cac), critical micelle concentration (cmc), the effective degree of counter-ion binding (β) at different temperatures were obtained. The thermodynamic parameters, i.e., Gibbs energy of aggregation and micellization, standard enthalpy of aggregation, and standard entropy of aggregation of surfactant/polymer system were estimated, employing pseudophase separation model. The negative values of Gibbs energy and standard enthalpy suggest that the surfactant/polymer aggregation process is spontaneous and exothermic respectively.